Mr. tucket eaudiobook - Paulsen, Gary (Francis Tucket, 2014)
It is 1848, and Francis Tucket is heading west on the Oregon Trail with his family. Yesterday he celebrated his 14th birthday on the tailgate of a Conestoga wagon in the foothills of the Rockies. Today, he is going to practice with his new birthday present, a Lancaster rifle. Falling far behind the wagon train, Francis loses sight of his family and is kidnapped by Pawnee Indians. Saved by a one-armed mountain man named Mr. Grimes, Francis takes off with his rescuer on a wild adventure peopled by actual historical characters, including Jim Bowie, and set against an historically-accurate background of the Old West.